Murder at Half Moon Gate [large type] - Penrose, Andrea (Penrose, Andrea. Wrexford & Sloane historical mystery., 2018)
"A wealthy lord who is a brilliant scientist . . . an enigmatic young widow who secretly pens satirical cartoons . . . a violent killing disguised as a robbery . . . Nothing is as it seems in Regency London, especially when the Earl of Wrexford and Charlotte Sloane join forces to solve a shocking murder"--